One Second Ahead Enhance Your Performance at Work with Mindfulness - Hougaard, Rasmus; Carter, Jacqueline; Coutts, Gillian; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
One Second Ahead is about applying mindfulness techniques (mindfulness techniques enable people to manage their attention, improve their awareness, and sharpen their focus and clarity) to work life.
Keywords: Psychology; Personnel management; Office management; Industrial psychology; Psychology; Industrial, Organisational and Economic Psychology; Human Resource Management; Office Management; Electronic books